2015
DOI: 10.1002/jcc.24025
|View full text |Cite
|
Sign up to set email alerts
|

Beyond static structures: Putting forth REMD as a tool to solve problems in computational organic chemistry

Abstract: Computational studies of organic systems are frequently limited to static pictures that closely align with textbook style presentations of reaction mechanisms and isomerization processes. Of course, in reality chemical systems are dynamic entities where a multitude of molecular conformations exists on incredibly complex potential energy surfaces (PES). Here, we borrow a computational technique originally conceived to be used in the context of biological simulations, together with empirical force fields, and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 144 publications
(182 reference statements)
1
59
0
Order By: Relevance
“…The geometrical conformations of both 1. trans and 1. cis , were determined by replica-exchange molecular dynamic (REMD) computations performed at the density functional tight binding (DFTB) level (REMD@DFTB). 44 Several minima were identified and optimized statically at the density functional theory level (see ESI for details†). The lowest-lying structures revealed that when the azobenzene is in its extended trans conformation ( 1. trans ), the bithiophene unit is forced to twist out of coplanarity with a dihedral angle ( θ ) of 55° (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The geometrical conformations of both 1. trans and 1. cis , were determined by replica-exchange molecular dynamic (REMD) computations performed at the density functional tight binding (DFTB) level (REMD@DFTB). 44 Several minima were identified and optimized statically at the density functional theory level (see ESI for details†). The lowest-lying structures revealed that when the azobenzene is in its extended trans conformation ( 1. trans ), the bithiophene unit is forced to twist out of coplanarity with a dihedral angle ( θ ) of 55° (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…If a move is rejected, both ensembles are restored to their initial state. The i-PI implementation of replica exchange has already been used to sample organic chemical reactions and conformational transitions with den-sity functional tight binding [33]. Here, we provide a simple demonstration that illustrates the power of this approach using both classical and path integral REMD.…”
Section: Replica Exchange Molecular Dynamicsmentioning
confidence: 92%
“…• replica exchange MD (R. Petraglia, R. Meissner, M. Ceriotti) [33]; accelerated convergence of averages by performing Monte Carlo exchanges of configurations between parallel calculations…”
Section: Program Featuresmentioning
confidence: 99%
“…[ 43–45 ] The efficiency of DFTB‐MD for large systems has been greatly improved by combination with fragment molecular orbital [ 46–49 ] or divide‐and‐conquer (DC) techniques. [ 50,51 ] Enhanced sampling methods have been recently applied to DFTB‐MD, resulting in novel DFTB‐REMD, [ 52 ] DFTB‐REUS, [ 53,54 ] and DFTB‐MetaD methods. [ 55,56 ]…”
Section: Introductionmentioning
confidence: 99%